CASE BASED LEARNING (CBL) DALAM KELAS BAHASA MANDARIN PEMBELAJAR ANAK - Qorie, Tiffany; Zhou , Wei (Universitas Negeri Surabaya, 2024)
This research provides valuable insights into using the Case Based Learning (CBL) Model in teaching Mandarin to children. With a focus on bridging the gap between theory learned in the classroom and factual problems in the field, this approach appears to successfully provide relevant solutions based on scholarly theory for factual cases. The finding that the CBL model has developed skills in organizing topics and issues, making decisions, and identifying problems indicate its effectiveness in preparing learners to face real-world challenges. This is important because it helps learners relate their knowledge to more meaningful and applicable contexts. The positive perception of learners towards CBL, especially in terms of increasing active class participation, suggests that this approach is not only beneficial in terms of learning but also motivates learners to engage more deeply in the learning process. However, the finding that openness to accepting opinions from others needs to be improved indicates that there is still room for further development in implementing this model. This could be a focus point for improvement in the future, such as strengthening collaborative elements in learning. Overall, this research makes a meaningful contribution to strengthening empirical evidence of the effectiveness of the CBL Model in the context of teaching Mandarin to children and highlights the importance of considering learners' perceptions in designing effective learning approaches.